Legal Analysis of Government Policy on Large Scale Social Restrictions in Handling Covid-19 - Ratna Desinta Mega Kumala (The Indonesian Journal of International Clinical Legal Education, 2020)
Corona Virus Disease 2019 (COVID-19) has been declared by the World Health Organization (WHO) as a pandemic so prevention efforts need to be made to avoid an increase in cases. In the context of prevention efforts carried out the implementation of health quarantine as regulated in Act Number 6 of 2018 concerning Health Quarantine. The implementation of health quarantine is a joint responsibility of the Central Government and Regional Governments as a form of protection of public health from diseases and / or public health risk factors that have the potential to cause public health emergencies. Health quarantine is carried out through disease observation activities and public health risk factors for transportation, people, goods, and or the environment, as well as responses to public health emergencies in the form of Health quarantine measures. One of the acts of health quarantine is in the form of large-scale social restrictions. The spread of Corona Virus Disease 2019 (COVID-19) in Indonesia is now increasing and expanding across regions and across countries accompanied by the number of cases and / or the number of deaths. The increase has an impact on political, economic, social, cultural, defense and security aspects, as well as the welfare of the people in Indonesia, so it is necessary to accelerate the handling of Corona Virus Disease 2019 (COVID-19) in the form of large-scale social restrictions in order to reduce the spread of Corona Virus Disease 2019 (COVID-19) is expanding.